Comparative study of ultra-lightweight pulp foams obtained from various fibers and reinforced by MFC. (15th February 2018) - Liu, Y.; Kong, S.; Xiao, H.; Bai, C.Y.; Lu, P.; Wang, S.F.
Highlights: The feasible approach for fabricating cellulose-based green pulp foam was developed. Pickering pulp foams were successfully stabilized and reinforced by MFC. Comparison of different fiber and surfactant types for forming pulp foams was made. The resulting foam was ultra-lightweight (0.014 g/cm 3 ) and highly porous (> 90%). Abstract: A range of cellulose-based, ultra-lightweight pulp foams with different morphologies were prepared and reinforced with microfibrillated cellulose (MFC). By careful design of the pulp foam forming process, free-standing ultra-lightweight pulp foams were obtained through high velocity mixing and air/oven drying from cellulose fiber in the presence of surfactant, MFC, and retention aid. The effects of different types of fibers and surfactants on the air uptake volumes and mechanical properties of the foam were systematically investigated. The structures characterized using an optical microscope and scanning electron microscope (SEM) showed that the foam was composed of wood fibers into two- or three-dimensional microstructures within random orientations surrounding gas bubbles. The results indicated that in spite of the strength of the foam could be manipulated by varying the surfactants and processing parameters, the addition of MFC indeed improved strength of pulp foams further. The process developed in this work provides a cost effective approach to fabricate the strong and ultra-lightweight pulp foam, with a density lower than 0.02 g/cm 3, using a standard handsheet former.